Resource allocation and connection admission control in satellite networks. - Koraitim, H.
This work focuses on resource allocation and connection admission control (CAC) issues in broadband satellite networks. Broadband services can now be provided by satellite systems operating in the Ka band, due to the large bandwidth available at such frequencies. In this context, we propose a resource allocation algorithm which integrates three classes of services at the MAC layer: constant bit rate (CBR), bursty data, and best effort services. The double movable boundary strategy (DMBS) is proposed to establish a resource-sharing policy among these service classes over the satellite uplink channel. The DMBS is a dynamically controlled boundary policy which adapts the allocation decision to the variable network loading conditions. Connection-oriented and connectionless services can be supported by the system. The CAC and slot allocation decisions are taken at the beginning of each control period after monitoring the filling level of traffic request queues. A threshold level for the bursty data request queue is defined to regulate the CAC process. The impact of the queue threshold value on the performance of the DMBS allocation policy is particularly evaluated in this study. A dynamic variation of this value is also proposed to enhance the system response to interactive applications. We present a brief analytical formulation for the DMBS model, together with simulation study details and performance evaluation results. The obtained results indicate a good efficiency, in terms of overall channel throughput and CBR blocking probability, for both fixed and dynamic data queue threshold approaches. The dynamic approach, however, outperforms the fixed one in terms of overall encountered bursty data delay
Keywords: CBR; Ka band; MAC layer; VSAT network; Bandwidth; Best effort services; Blocking probability; Broadband satellite networks; Broadband services; Bursty data delay; Channel throughput; Connection admission control; Connection-oriented services; Connectionless services; Constant bit rate; Double movable boundary strategy; Dynamic data queue threshold; Dynamically controlled boundary policy; Efficiency; Fixed data queue threshold; Interactive applications; Performance evaluation results; Queue threshold level; Resource allocation algorithm; Resource-sharing policy; Satellite uplink channel; Simulation; Slot allocation; Traffic request queues; Variable network loading